Risk Factors Associated with Zinc Status of Filipino Preschool and School-aged Children. - Marcos, J.M.
In the 2008 National Nutrition Survey, zinc deficiency among preschool and school-aged children was reported as a significant public health problem. This study aimed to identify the risk factors correlated to zinc deficiency in preschool (6 mo ? 5 yr old) and school-aged (6 ? 12 yr old) Filipino children. Statistical analyses were done to measure the association of zinc status of children with demographic, anthropometric, biochemical, dietary, environmental, and socioeconomic data of the 2008 National Nutrition Survey using test on means, chi-square test and test on distributions and logistic regression analysis. Older preschool and school children were more at-risk to zinc deficiency. Stunting, anemia, vitamin A deficiency, and iodine deficiency disorder were more prevalent in zinc-deficient children. Lower average intakes of most nutrients; consumption of lesser amounts of fish, meats, and poultry; and higher intake of corn and corn products and green leafy vegetables were also noted among zinc-deficient children. Children belonging to households with lower wealth quintile and with household head working as agricultural farmer or fisherman are also more at-risk. Being male, residence in rural areas and educational attainment of household head below high school also lower zinc status in school-aged children. Older age, high prevalence of stunting, anemia, and vitamin A deficiency, and inadequate and poor quality diets are significantly associated to zinc deficiency among preschool and school-aged children. Poor households and household head working as agricultural farmer or fisherman are likewise significant risk factors among these children. Being male, residence in rural areas and educational attainment of household head below high school also significantly correlates to low zinc status of school children.
Keywords: Science -- Periodicals; Filipino preschool and school children; Micronutrient deficiencies; Nutrient and food intakes; Socio-economic status; Stunting; Zinc deficiency